The “Nusantara” Cash-Waqf Model: Designing Alternative Scheme for Infrastructure Financing - Pratama, Raditya Hendra; Qadri, Resi Ariyasa; Khabibi, Akhmad (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2023)
Abstract. This study aims to design a cash waqf governance framework for f inancing infrastructure in Indonesia's new capital, Nusantara. The academic literature review is used to accomplish the research goals. The findings indicated that the waqf program can fund capital infrastructure development projects. Our results offer a cash waqf model linked to the Muḍarabah contract to pay for the state capital's relocation. The government can utilize this information as a springboard for developing financing regulations based on Islamic finance. By integrating pertinent stakeholders, further studies can employ the model created through grounded theory. By conceiving of a cash Waqf system for funding public infrastructure development, our article advances Islamic finance literature.Abstrak. Kajian ini bertujuan untuk merancang kerangka tata kelola wakaf uang untuk pembiayaan infrastruktur di ibu kota baru Indonesia, Nusantara. Kajian literatur akademik digunakan untuk mencapai tujuan penelitian. Temuan menunjukkan bahwa program wakaf dapat mendanai proyek pembangunan infrastruktur modal. Hasil kami menawarkan model wakaf tunai terkait dengan kontrak mudharabah untuk membayar relokasi ibukota negara. Pemerintah dapat memanfaatkan informasi ini sebagai batu loncatan untuk mengembangkan regulasi pembiayaan berdasarkan keuangan syariah. Dengan mengintegrasikan pemangku kepentingan terkait, studi lebih lanjut dapat menggunakan model yang dibuat melalui grounded theory. Dengan memahami sistem wakaf tunai untuk mendanai pembangunan infrastruktur publik, artikel kami memajukan literatur keuangan Islam.